EPEN-22. Molecularly aggressive ependymomas treated with Image guided pencil beam proton therapy: consecutive patient Indian experience. (3rd June 2022) - Sudarsan, Rishan Thimma; Chilukuri, Srinivas; Noufal, M P; Adhithyan, R; Uppuluri, Ramya; Panda, Pankaj Kumar; Patil, Sushma; Sharma, Dayananda; Roopesh Kumar, V R; Jalali, Rakesh
Abstract: AIM: To assess the toxicities and early clinical outcomes in patients of primary and recurrent ependymomas treated with image guided pencil beam scanning proton beam therapy (PBS-PBT). MATERIALS AND METHODS: Between January 2019- December 2021, we analyzed consecutive patients of ependymomas treated with image guided PBS-PBT. They were also analyzed molecularly, and all recurrent/re-irradiated patients were considered for craniospinal irradiation (CSI). Acute toxicities were assessed based on NCI CTC v5.0, local control and radiological response by 3-monthly MRI post therapy. RESULTS: Seventeen consecutive patients with ependymoma (13 Grade III and 4 Grade II) (median age-9 years) were analyzed. 9 patients were primary, 7 were treated at first recurrence and 1 at second recurrence. Majority had posterior fossa (PF) tumors (12) followed by supratentorial (ST) (3) and spine (2). Among PF ependymomas, 10 had global loss of H3K27me3, whereas amongst ST, 1 had YAP1 fusion, 1 had L1CAM positivity and other, negative L1CAM and p65/RELA on immunohistochemistry. Gross/near-total resection was achieved in 87% patients. Primary ependymomas were treated with focal radiotherapy; and among recurrent cases, 7 received CSI followed by primary site boost to a total median dose of 55CGE (50.2-55.8CGE). Grade 2 dermatitis, grade 2 and 3 hematological toxicities (CSI) were noted in 3, 2 and 2 patients respectively. Grade 2 fatigue noted in 53% of all and 71% receiving CSI. With a median follow-up of 10 months (2-24 months), local control (LC) and disease-free survival (DFS) was 87.5% (primary-100%, recurrent-75%) and overall survival (OS) was 94% (primary-100%, recurrent-88%). CONCLUSION: Our experience of treating patients of ependymoma with complete resection followed by PBS-PBT including CSI is encouraging with low acute toxicities. Recurrent/molecularly aggressive cases may be considered for CSI. Keywords: PT, proton beam therapy, ependymomas, primary and recurrent